Project Finance Worldwide and in CEE - Chroust, Petr (2013)
The main aim of the thesis is to test a hypothetical relationship between the volume of project finance in various countries and the factors of general economic environment (especially sovereign credit rating and GDP per capita). The thesis describes the development of the project finance markets between 2000 and 2012 and measures the intensity with which project finance is used in various countries. Based on this data, correlation analysis tests whether this "intensity" in a given country depends on GDP per capita or sovereign credit rating. The last chapter is devoted to the study of project finance in CEE region. Project loan volumes in CEE were analyzed in the context of region's GDP, credit ratings, lending rates and public indebtedness. The correlation analysis revealed that the "intensity of project finance" in a given country is generally independent of GDP per capita and country rating. The same conclusion was drawn both worldwide and in CEE. Additional analysis in CEE found a moderate relationship between infrastructure projects and public indebtedness. Lending rates seem irrelevant for the concentration of project finance in CEE countries.